A behavioural and non-behavioural analysis of the London gold market - O'Connor, Fergal (Trinity College (Dublin, Ireland). Trinity Business School, 2015)
This thesis makes a number of contributions to the literature on the economics and finance of the gold market, with a special emphasis on the London gold market. It provides the first effort to produce a substantiate literature review of the published academic papers relating to the financial economics of gold ignoring any other gold related issues outside this, such as the gold standard. A review of the current state of research on the following issues is given with respect to gold: inflation, interest rates, hedging, diversification, safe havens, gold’s relationship to other assets, volatility drivers, market efficiency, speculative bubbles, behavioural issues, market linkages and finally the economics of gold mining. From this broad reading three research questions were formed and investigated.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin